The colloidal stability of water-in-oil-in-water double emulsion stabilized by Pickering emulsifier mixture in encapsulating ethanolic kenaf leaves extract - Elaine, Elaine; Tan, Chin Ping; Akanda, Md Jahurul Haque; Nyam, Kar Lin (Springer, 2024)
Double emulsion (DE) has recently attracted attention due to its ability to encapsulate hydrophilic and hydrophobic substances and controlled release properties. However, food-grade DE is prone to destabilization due to its complex structure, which makes practical application in the industries difficult. This study investigates the stabilization of DE containing ethanolic kenaf leaf extract using different concentrations of Pickering emulsifier mixture (PEM). PEM consists of sodium caseinate, tween-20, and beta-cyclodextrin at the fixed ratio of 57.9:27.6:14.5% (w/w/w). Key parameters such as droplet size, polydispersity index, creaming index, encapsulation efficiency, and droplet morphology were monitored during 5-week storage at 25 °C. All DE samples remained phase-stable and exhibited increasing viscosity throughout the storage. The droplets displayed a spherical shape, and functional group assessment indicated changes in the molecular interactions after ultrasonic emulsification. DE stabilized by 2.5% and 4.0% (w/w) PEM consistently maintained droplet size and distribution, achieving encapsulation efficiency exceeding 98%. Specifically, DE with 4.0% (w/w) PEM exhibited excellent resistance to pH changes. In conclusion, PEM-stabilized DE remained stable for up to 5 weeks at 25 °C, which facilitates the beneficial uses of double emulsion in food, cosmetic, and medical applications.